(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The aim of this research is to determine the extent of the effect of the organizational climate (organizational structure, leadership style, participation in decision-making, communication technology, incentives, training) in the performance of human resources, at the Tishreen University. The researcher distributed (100) questionnaires to a sample of managers, and administrative staff responsible in university under study. (89) questionnaires were retrieved and (7) questionnaires were excluded, Thus, the number of questionnaires that have been discharged is (82). The researcher analyzed the data using the Statistical Analysis Program (SPSS 25). At the end of this research, the researcher reached a number of conclusions, the most important of which are: There is a significant effect of the organizational climate (organizational structure, leadership style, participation in decision-making, communication technology, incentives, training) in the performance of human resources, at the university under study. The researcher also made a number of recommendations, including: The need for the university to develop organizational structures and design new organizational structures characterized by greater flexibility, the need to improve the physical environment for work at the university, and strive to increase the degree of diversity in business, tasks and job duties of workers, and provide an opportunity for workers to renew, innovate, develop and change..